2022
DOI: 10.1038/s41598-022-06397-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of 233 nm far-UVC LEDs for eradication of MRSA and MSSA and risk assessment on skin models

Abstract: A newly developed UVC LED source with an emission wavelength of 233 nm was proved on bactericidal efficacy and skin tolerability. The bactericidal efficacy was qualitatively analysed using blood agar test. Subsequently, quantitative analyses were performed on germ carrier tests using the MRSA strain DSM11822, the MSSA strain DSM799, S. epidermidis DSM1798 with various soil loads. Additionally, the compatibility of the germicidal radiation doses on excised human skin and reconstructed human epidermis was proved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 60 publications
1
34
2
Order By: Relevance
“…Following the increased interests in room disinfection and skin antisepsis during the COVID-19 pandemic, studies have been conducted to prove the bactericidal [1][2][3][4][5][6] and virucidal 7-9 potential of far-UVC radiation (100-240 nm). UVC radiation (100-280 nm) is known to be absorbed by nucleic acids and proteins.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Following the increased interests in room disinfection and skin antisepsis during the COVID-19 pandemic, studies have been conducted to prove the bactericidal [1][2][3][4][5][6] and virucidal 7-9 potential of far-UVC radiation (100-240 nm). UVC radiation (100-280 nm) is known to be absorbed by nucleic acids and proteins.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Furthermore, 233 nm produces no or only little superficial DNA damage in excised human skin and reconstructed human epidermal (RHE) skin models up to 60 mJ/cm 2 in comparison to the same irradiation dose at 254 nm (≥factor 20); moreover, the DNA damage is below 0.1 of the minimal erythema dose UVB, which is considered acceptable. After 24 h, the DNA damage degraded completely in the RHE; multiple irradiation on four consecutive days with 60 mJ/cm 2 shows no detectable DNA damage 11 …”
Section: Introductionmentioning
confidence: 98%
“…After 24 h, the DNA damage degraded completely in the RHE; multiple irradiation on four consecutive days with 60 mJ/cm 2 shows no detectable DNA damage. 11 In this study, UVC irradiation at 233 nm was compared with 222 nm for its eradicating effect on the species C. albicans and C. parapsilosis; 254 nm served as a positive control for the possibility of complete eradication.…”
mentioning
confidence: 99%
“…However, almost 20 years ago, Sosnin et al [ 6 ] found that there is short-wavelength UVC radiation, which damages eukaryotic cells less than prokaryotic cells. Meanwhile, it has been found that human skin tolerates UV radiation in the so-called far-UVC range of about 200–230 nm relatively well [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. This radiation is almost completely absorbed in the stratum corneum and does not reach deeper skin layers.…”
Section: Introductionmentioning
confidence: 99%